Importance of Developing a Local Instrument of Disaster-resilient School, Letter to Editor - Samaneh Mirzaei; Leila Mohammadinia (Shahid Sadoughi University of Medical Sciences, 2019)
The creation of various risks followed by financial and human life losses has globally doubled the need for paying attention to education in order to promote the preparedness in higher order documents. With regard to disasters, the importance of education has been emphasized repeatedly in the operational program of Hyogo (2005-2015) (1) and Sendai framework (2015-2030) (2) by reducing the disaster risks and creating the resilience in line with the consistent development. In this realm, schools play a major role in educating the generations that can exert a significant effect on increasing disaster-resilience in the course of time (3). Schools, as educational places, host many students annually and students spend most of their time in schools. Schools can serve not only as educational sites, but also as emergency lodgings for people in emergency cases (4). However, some schools cannot be used for this purpose since they damage the building constructs   leading to lack of resilience in disasters. On the other hand, many students get injured or die annually due to the natural disasters or man-made events. For instance, the earthquake and tsunami in Japan (2011) damaged 6000 schools and killed 607 people (575 students and 24 teachers) (5) and the earthquake of Bohol in the Philippines (2013) also damaged 604 primary schools and 92 high schools (6). These are examples of school damages while safety, preparedness, and school resilience against disasters can be enhanced by implementing and supervising the standards of constructs and infrastructures. Furthermore, developing the performance process in schools along with increasing sensitivity and attention can be helpful in this area (7).Thus, schools can be safe places for students and suitable shelters and lodgings for harboring disaster survivors. It should also be noted that disaster-resilient schools could increase the community preparedness for responding properly at the time of disasters and events through educational programs in the field of risk perception and preventive measures (8). Therefore, development of an instrument for measuring the resilience level is a challenging issue, which is considered as a serious problem for researchers in their studies on disasters. Consequently, it is mandatory to develop a local and suitable instrument for measuring the components that affect school resilience in disasters and introduce it to the interested parties